A Study on Livelihood Diversification and its Determinants at Farm level in Uttarakhand (Indian Journal of Extension Education, 2024)
Farm diversification is seen as a vital strategy for fostering rapid economic growth and development in hilly regions. This includes shifting from traditional crops to more valuable ones and engaging in additional activities like dairy farming, poultry, fishery, sheep and goat rearing, horticulture, and related pursuits. The present study was undertaken in Uttarakhand in 2023 with 140 sponsored farmers at SAMETI to investigate the extent and nature of livelihood diversification among the farmers. It was found that Simpson’s diversity index was 0.89 and overall farmers were involved in 14 different types of farming enterprises, with 79 per cent involved in cereal cultivation followed by vegetables (55.71%), and fruits and plantation (40%) and a very less percentage of farmers involved in fishery (13.57%), forestry (9.29%), and mushroom (5.71%). The number of training attended (β6 = 0.767) by a farmer had a major impact on the diversification of the farmers. The study suggests several less utilized farming enterprises, where more involvement of farmers should be ensured thus improving their profits. Farmer training will play a significant role in achieving the above goals.